THE EFFECT OF WORK STRESS AND LEADERSHIP STYLES ON EMPLOYEE PERFORMANCE PT. BNI (PERSERO) TBK. MANADO BRANCH - Tambalean, Febriany Prichilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
EmployeesÂ  are the human resources of company and its most valuable asset. Company need to concern to all the factors that can affect the performance of their employee. This research is purposed to analyze the effect of work stress and leadership styles on employee performance at PT. BNI (Persero) Tbk. Branch Manado. The study took 50 employees as a sample from PT. BNI (Persero) Tbk. The data was analyzed by using multiple regression analysis. Work stress and leadership styles have negative significant effect on employee performance at PT. BNI (Persero) Tbk. Branch Manado influence. Higher level of stress existed with no managerial concern for solution consequently lowering the employee performance. Company have to aware the relationship between their employees, because it partially can lead to the conflict. Conflict that can not be handle by the company can damage and destructive the company and employeeâ€™s as well. Company should provide a comfortable working environment, give variety of task to employees that they are doing a good job and not demanding to much of their employees. Keywords: employee, performance, stress, leadership